Droplet–droplet interactions investigated using a combination of electrochemical and dynamic light scattering techniques. The case of water/BHDC/benzene:n-heptane system1. Issue 15 (21st April 2015) - Florez Tabares, Juán Sebastián; Correa, N. Mariano; Silber, Juana J.; Sereno, Leonides E.; Molina, Patricia G.
<x xml:space="preserve">Abstract</x> In this contribution electrochemical and dynamic light scattering methods are used on the system water/BHDC/benzene:n-heptane to unravel the unusual interdroplet interactions.